Pengaruh Fundamental Mikro, Fundamental Makro Terhadap Nilai Perusahaan dengan Karakteristik Perusahaan, Kinerja Keuangan, Struktur Modal Variable pada Perusahaan Manufaktur yang Terdaftar Di BEI Tahun 2019-2023 - Cailah Nasywa Afrila; Hwihanus Hwihanus (Jurnal Riset Ekonomi dan Akuntansi, 2025)
Investigating the impact of micro and macro fundamentals on the value of manufacturing companies listed on the Indonesia Stock Exchange (IDX) between 2019 and 2023 is the purpose of this study. In this study, mediating factors include capital structure, financial performance, and firm characteristics. Firm size, Net Profit Margin (NPM), and Debt Ratio (DR) are examples of micro fundamentals, while GDP, inflation, and interest rates are examples of macro fundamentals. This study assesses the relationship between variables using path analysis based on SmartPLS. The results show that micro fundamentals significantly affect financial performance, capital structure, and firm characteristics, while macro fundamentals only affect capital structure. In addition, firm characteristics are proven to affect financial performance, but do not directly affect firm value. A company's financial performance greatly affects its value. The results show that strategic internal management and adaptation to macroeconomic changes are essential to increasing business value. This study helps stakeholders, including corporate management and policy makers, in building strategies that maximize firm value amidst increasingly complex global economic challenges and market competition.